2018
DOI: 10.2478/midj-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Service Recovery Strategies versus Customers’ Expectations, Race for Sustainability: a Qualitative Study on Micro Brands

Abstract: Purpose of the research is to investigate service recovery strategies in case of small restaurant brands, customer perception regarding these strategies and their expectations intensely. As the study is qualitative and exploratory in nature, data were collected via in-depth interviews from duo perspective; i.e. service providers’ and customers’ perspective. The results showed that even though the managements are very cautious as regards the service recovery strategies, and customers’ complaints, but sometimes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 70 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Place branding was initially focused on the country level (Anholt, 2010;Hanna and Rowley, 2008;Kotler and Gertner, 2002) and tourism destination brands (Acharya and Rahman, 2016;Anholt, 2010;Bose et al, 2016). However, it is applicable to non-touristic places (Baker, 2007) such as town centres (Teller et al, 2010) involving the physical and operational attributes of a place in place branding (Ashworth and Voogd, 1990;Kotler et al, 1999). Recently, explorations of the nature and future of place branding are beyond its tourism approach (see Kavaratzis and Florek, 2021), with scant attempts to bridge the gap between theory and practice (Hankinson, 2010).…”
Section: Place Marketing and Brandingmentioning
confidence: 99%
See 2 more Smart Citations
“…Place branding was initially focused on the country level (Anholt, 2010;Hanna and Rowley, 2008;Kotler and Gertner, 2002) and tourism destination brands (Acharya and Rahman, 2016;Anholt, 2010;Bose et al, 2016). However, it is applicable to non-touristic places (Baker, 2007) such as town centres (Teller et al, 2010) involving the physical and operational attributes of a place in place branding (Ashworth and Voogd, 1990;Kotler et al, 1999). Recently, explorations of the nature and future of place branding are beyond its tourism approach (see Kavaratzis and Florek, 2021), with scant attempts to bridge the gap between theory and practice (Hankinson, 2010).…”
Section: Place Marketing and Brandingmentioning
confidence: 99%
“…Within the city scale, micro-brands act as micro-places. Micro-brands have been explored in food products (Kumar and Babu, 2013) and small restaurants (Bin Shahriar et al , 2018), also applying a microlens of brand personality showcasing the advantages of this approach for studying specific sectors (Valette-Florence and De Barnier, 2013). However, scant references to “micro” places appear in place branding literature, such as the Qatari micro-state (Peterson, 2006) or the micro-region of Hateg in Romania (Vesa, 2017).…”
Section: Place Marketing and Brandingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this series researchers tried to explain different aspects of service failure and recovery from the perspective of micro restaurant and food service brands. Their recent study (Shahriar, et al, 2018) on customers' expectations from service recovery revealed that, restaurants those have better understanding of customers' needs and those who are involving customers with the recovery process are getting more customer satisfaction and loyalty. Another case study by Shahriar, et al (2017) on small restaurant brands, showed that small restaurant brands which are emphasizing on customers' engagement to design effective service recovery policies, additionally customer engagement essentially help the service organization to reduce the cost of recovery action.…”
Section: Case Backgroundmentioning
confidence: 99%
“…So it is also important for the service brans to design effective service recovery processes. In previous studies Shahriar et al (2018) tried to focus on the service recover design from the small brands' perspective. Findings from this researchers showed that services providers are trying to become more innovative while designing the service recovery.…”
Section: Service Failure and Recovery For A Small Brandmentioning
confidence: 99%